2019
DOI: 10.4236/pp.2019.1011039
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Pharmacovigilance by Nurses and Midwives of the Cocody University Teaching Hospital in Abidjan

Abstract: Objective: To assess the perception on pharmacovigilance by the nurses and midwives at the University Teaching Hospital (CHU) of Cocody in 2017. Methodology: Descriptive and analytic cross-sectional study conducted in 17 services of the University Teaching Hospital (CHU) of Cocody using an anonymized and standardized questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…In contrast to a previous study wherein 76.74% of the nurses/midwives reported ADRs that they encountered 6 , only three midwives in the present study (9%) stated that they had previously reported ADRs to TPC. One of them declared that she was worried about her patient's health, so she sent the report (Table 4).…”
Section: Attitude/practice Of Subjectscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to a previous study wherein 76.74% of the nurses/midwives reported ADRs that they encountered 6 , only three midwives in the present study (9%) stated that they had previously reported ADRs to TPC. One of them declared that she was worried about her patient's health, so she sent the report (Table 4).…”
Section: Attitude/practice Of Subjectscontrasting
confidence: 99%
“…On the other hand, among those who did not send any report in the past, the opinion that ADRs were already mentioned in the short product information, ADRs were not entirely serious, and reporting ADRs unnecessarily put them off from reporting (Table 4). Similar reasons were stated by the nurses/midwives of another study conducted in Côte d'Ivoire, a sub-Saharan African country 6 . Furthermore, two midwives in our study stated that the lack of confidence in analyzing the relationship between the drug and the side effect prohibited them from reporting it (Table 4).…”
Section: Attitude/practice Of Subjectssupporting
confidence: 74%
See 3 more Smart Citations